Morphotaxonomy of the Simulium (Simulium) tuberosum species group (Diptera: Simuliidae) in Thailand - Tangkawanit, Ubon; Kuvangkadilok, Chaliow; Baimai, Visut; Adler, Peter H. (Zootaxa, 2009)
Seventeen cytogenetically distinct taxa of the Simulium (Simulium) tuberosum species group in Thailand were examined morphologically, including Simulium doipuiense (cytoforms A and B), S. manooni, S. rufibasis, S. setsukoae, S. tani (cytoforms A-I), S. weji, S. yuphae, and one unknown species. Identification keys to larvae, pupae, males, and females are provided, along with diagnostic characters for each taxon and a morphology-based phylogeny.